Results of non-interventional observational study of ursodeoxycholic acid in primary biliary cirrhosis - Yelena N. Shirokova; Anna F. Sheptulina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate clinical efficacy and safety of ursodeoxycholic acid («Livodexa®») in a dose of 15 mg/kg/day for 3 months in the treatment of primary biliary cirrhosis (PBC) of the I to III stage. Material and methods. Open single center clinical trial included 30 patients with PBC of the I-III stage. All patients received «Livodexa®» in the daily dose of 15 mg/kg taken two times per day for 3 months. Efficacy and safety investigation of the drug was carried out at the day 30 (visit 2) and at the day 90 (visit 3) according to the laboratory tests results, quality of life assessment by SF-36 questionnaire, registration of frequency and severity of the adverse events (AE). Results. The median age (interquartile range) of PBC patients enrolled in the original study was 53 (48-61) years, the women prevailed: 29 (96,6%). The majority (43,2%) of patients had PBC of the histological grade II according to the Ludwig system. Treatment with «Livodexa®» in a dose of 15 mg/kg/day resulted in a statistically significant decrease of biochemical marker levels: alanine transaminase, aspartate aminotransferase, alkaline phosphatase, gamma-glutamyltranspeptidase, total and conjugated bilirubin at the 30th day of treatment (visit 2; p